Avaliações agronômicas e físico-químicas de híbridos de pimenta Capsicum baccatum - Muñoz, Thiago Simões Acuña (Universidade Federal de São Carlos, 2026)
Peppers belonging to the genus Capsicum are one of the most widely used condiments in the world. The objective of this research work was to identify superior hybrid genetic material of pepper plants of the species C. baccatum, through plant architecture and yield parameters, as well as fruit morphometry and quality. The hybrids were grown in a protected system in pots with fertigation. The development of intraspecific hybrids in Capsicum baccatum proved to be a highly viable strategy to overcome the technological scarcity in the Brazilian pepper sector. The experimental hybrids F1 204 and F1 206 exceeded production and quality expectations—with the exception of total phenolic compounds and carotenoid contents—presenting themselves as genetic materials with high commercial potential and extreme promise for the hybrid seed agribusiness and for the supply of standardized raw material in national vegetable production.
Agronomic and physicochemical evaluations of Capsicum baccatum pepper hybrids.
Keywords: Heterose; Hortaliça de frutos; Melhoramento genético; Dedo-de-moça; Heterosis; Fruit vegetable; Plant breeding; CIENCIAS AGRARIAS::AGRONOMIA; 2. Fome Zero e Agricultura Sustentável